Searching for the ‘Pendekar Silat’ in Malaysian visual media: A prefatory insight towards sustainable cultural heritage / Muhamad Azhar Abdullah... [et al.] - Abdullah, Muhamad Azhar; Anuar, Roslaili; Md. Noor, Harrinni; Wan Zakaria, Wan Zamani (UiTM Perak Press, 2022)
The pendekar silat is considered as a culture hero who defines the traditional Malay warrior and the Malays, along with the martial arts and heritage values. Rising interests in Malay cultural heritage within Malaysia has led to the ascension of the pendekar silat character in the insular setting including in local comics. This prefatory insight looks into how comic arts are digitally circulated leading to the appropriation of artworks from two published comics titled “Liga Pendekar – Perikatan Adiwira” and “Pendekar Melayu Terakhir” in regard to pendekar silat and pendekar Melayu or the Malay silat warrior. The researchers used keywords internet search to identify two most prominent artwork from the selected comics which have been widely appropriated. This initial inquiry revealed that the main keywords used in the internet search would yield the artwork from the covers of the two comic publications thus, delineating claims that the source of the artwork is digitally unknown or untraceable.